Palladium complex of sulphated schiff base with ortho-vanillin as catalyst for O-arylation of phenol. (2022) - Sharma, Deepali; Arora, Aayushi; Chamoli, Akansha; Rana, Preeti; Gairola, Sakshi; Oswal, Preeti; Kumar, Sushil; Kumar, Arun
Abstract: Organochalcogen compounds due to their hassle-free synthesis and air and moisture insensitive nature have attracted substantial attention in scientific world. They have profound applications in the development of catalytic systems that have emerged as efficient catalysts in various chemical transformations. Organochalcogen ligands have contributed to the backbone of several catalytic systems used for O -arylation reaction which is an effective tool for the synthesis of diaryl ether substituents. Synthesis of several bioactive compounds rely on this method. A thioether ligand L1 has been prepared by reaction of 3-(chloropropyl)amine hydrochloride with the insitu generated PhSNa. The L1 has been condensed with o -vanillin to synthesize ligand L2 having imine functionality. The structure of ligand L2 has been authenticated using proton and carbon-13 NMR techniques. The synthesis of an efficient N, S coordinated bidentate novel palladium complex 1 ([Pd(L2 )Cl2 ]), by the reaction of ligand L2 with [PdCl2 (CH3 CN)2 ] in chloroform-hexane system has been carried out. The structure of 1 has also been corroborated by 1 H, 13 C{ 1 H} NMR and mass spectroscopic techniques. Its catalytic potential has been tested for etherication of various aryl bromides with phenol. Cheaply available aryl chlorides have also been coupled to determine the efficiency of Pd(II) complex 1 . The complex 1 gave good yields while exhibiting excellent tolerance towards electronically diverse aryl halides with 0.5 mol% catalyst loading. The nature of catalysis has been found to be purely homogeneous on conducting mercury and triphenylphosphine poisoning tests.